The comparison of some anthropometric, body composition indexes and VO2max of Ahwaz elite soccer players of different playing positions - Abdolrahman Najafi; Saeid Shakerian; Abdolhamid Habibi; Mehrzad Shabani; Rouholah Fatemi (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : The purpose of this study was to compare some anthropometric, body composition indexes and VO2max of Ahvaz elite soccer players of different playing positions. Material : Participants were 60 male soccer players (age 24.31±4.20 years) from 4 teams in the two highest divisions in Iran. The sample included 8 goalkeepers, 18 defenders, 20 midfielders and 14 strikers. Anthropometric variables of subjects (height, weight and BMI) and body composition (%BF) were measured. Skinfold thickness measurements were taken using Harpenden skinfold calipers at three sites (triceps, subscapular and abdominal) and the VO2max of the subjects was estimated by participation in a multi-stage 20m shuttle-run test. One-way ANOVA and Tukey testes were used for possible differences in test variables between different player positions. Results : Results revealed that the goalkeepers were significantly (p<0.05) the tallest, heaviest and had lower VO2max than another positions. Beside the midfielders had significantly (p<0.05) higher VO2max than the goalkeepers. Also, no difference in estimated body fat percentage and BMI was observed between players of all positions. Discussion: Thus, it can be concluded that anthropometric and physiological differences are exist among soccer players who play in different positions. These differences fit with their different workload in a game. Therefore, programs must be include specific sessions for each positional role.